Computational characterization of enzyme-bound thiamin diphosphate reveals a surprisingly stable tricyclic state: implications for catalysis - Planas, Ferran; McLeish, Michael J.; Himo, Fahmi (Beilstein Journal of Organic Chemistry, 2019)
Thiamin diphosphate (ThDP)-dependent enzymes constitute a large class of enzymes that catalyze a diverse range of reactions. Many are involved in stereospecific carbon–carbon bond formation and, consequently, have found increasing interest and utility as chiral catalysts in various biocatalytic applications. All ThDP-catalyzed reactions require the reaction of the ThDP ylide (the activated state of the cofactor) with the substrate. Given that the cofactor can adopt up to seven states on an enzyme, identifying the factors affecting the stability of the pre-reactant states is important for the overall understanding of the kinetics and mechanism of the individual reactions.In this paper we use density functional theory calculations to systematically study the different cofactor states in terms of energies and geometries. Benzoylformate decarboxylase (BFDC), which is a well characterized chiral catalyst, serves as the prototypical ThDP-dependent enzyme. A model of the active site was constructed on the basis of available crystal structures, and the cofactor states were characterized in the presence of three different ligands (crystallographic water, benzoylformate as substrate, and (R)-mandelate as inhibitor). Overall, the calculations reveal that the relative stabilities of the cofactor states are greatly affected by the presence and identity of the bound ligands. A surprising finding is that benzoylformate binding, while favoring ylide formation, provided even greater stabilization to a catalytically inactive tricyclic state. Conversely, the inhibitor binding greatly destabilized the ylide formation. Together, these observations have significant implications for the reaction kinetics of the ThDP-dependent enzymes, and, potentially, for the use of unnatural substrates in such reactions.
Keywords: binding site; DFT; enzyme mechanism; quantum chemical calculations; ThDP-dependent

(untitled) - Pohl, M.; Sprenger, G. A.; Müller, M. (Curr. Opin. Biotechnol., 2004)

(untitled) - Kluger, R.; Tittmann, K. (Chem. Rev., 2008)

(untitled) - Müller, M.; Sprenger, G. A.; Pohl, M. (Curr. Opin. Chem. Biol., 2013)

(untitled) - Alvarez, F. J.; Ermer, J.; Huebner, G.; Schellenberger, A.; Schowen, R. L. (J. Am. Chem. Soc., 1991)

(untitled) - Breslow, R. (J. Am. Chem. Soc., 1958)

(untitled) - Nemeria, N.; Korotchkina, L.; McLeish, M. J.; Kenyon, G. L.; Patel, M. S.; Jordan, F. (Biochemistry, 2007)

(untitled) - Kaplun, A.; Binshtein, E.; Vyazmensky, M.; Steinmetz, A.; Barak, Z.; Chipman, D. M.; Tittmann, K.; Shaanan, B. (Nat. Chem. Biol., 2008)

(untitled) - Kern, D.; Kern, G.; Neef, H.; Tittmann, K.; Killenberg-Jabs, M.; Wikner, C.; Schneider, G.; Hübner, G. (Science, 1997)

(untitled) - Furey, W.; Arjunan, P.; Chen, L.; Sax, M.; Guo, F.; Jordan, F. (Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1998)

(untitled) - Lindqvist, Y.; Schneider, G.; Ermler, U.; Sundström, M. (EMBO J., 1992)

(untitled) - Muller, Y. A.; Lindqvist, Y.; Furey, W.; Schulz, G. E.; Jordan, F.; Schneider, G. (Structure, 1993)

(untitled) - Arjunan, P.; Umland, T.; Dyda, F.; Swaminathan, S.; Furey, W.; Sax, M.; Farrenkopf, B.; Gao, Y.; Zhang, D.; Jordan, F. (J. Mol. Biol., 1996)

(untitled) - Hasson, M. S.; Muscate, A.; McLeish, M. J.; Polovnikova, L. S.; Gerlt, J. A.; Kenyon, G. L.; Petsko, G. A.; Ringe, D. (Biochemistry, 1998)

(untitled) - Mosbacher, T. G.; Mueller, M.; Schulz, G. E. (FEBS J., 2005)

(untitled) - Jordan, F.; Zhang, Z.; Sergienko, E. (Bioorg. Chem., 2002)

(untitled) - Kochetov, G. A.; Usmanov, R. A.; Merzlov, V. P. (FEBS Lett., 1970)

(untitled) - Patel, H.; Nemeria, N. S.; Andrews, F. H.; McLeish, M. J.; Jordan, F. (Biochemistry, 2014)

(untitled) - Balakrishnan, A.; Paramasivam, S.; Chakraborty, S.; Polenova, T.; Jordan, F. (J. Am. Chem. Soc., 2012)

(untitled) - Jordan, F. (J. Am. Chem. Soc., 1974)

(untitled) - Jordan, F. (J. Am. Chem. Soc., 1976)

(untitled) - Friedemann, R.; Tittmann, K.; Golbik, R.; Hübner, G. (Int. J. Quantum Chem., 2004)

(untitled) - DuPré, D. B.; Wong, J. L. (J. Phys. Chem. A, 2007)

(untitled) - Delgado, E. J.; Alderete, J. B.; Jaña, G. A. (J. Mol. Model., 2011)

(untitled) - Jaña, G. A.; Delgado, E. J. (J. Mol. Model., 2013)

(untitled) - Lie, M. A.; Celik, L.; Jørgensen, K. A.; Schiøtt, B. (Biochemistry, 2005)

(untitled) - Wang, J.; Dong, H.; Li, S.; He, H. (J. Phys. Chem. B, 2005)

(untitled) - Alstrup Lie, M.; Schiøtt, B. (J. Comput. Chem., 2008)

(untitled) - Hou, Q.; Gao, J.; Liu, Y.; Liu, C. (Theor. Chem. Acc., 2012)

(untitled) - Planas, F.; Sheng, X.; McLeish, M. J.; Himo, F. (Front. Chem. (Lausanne, Switz.), 2018)

(untitled) - Topal, K. G.; Atilgan, C.; Demir, A. S.; Aviyente, V. (Biopolymers, 2010)

(untitled) - Sánchez, L.; Jaña, G. A.; Delgado, E. J. (J. Comput. Chem., 2014)

(untitled) - Jaña, G.; Jiménez, V.; Villà-Freixa, J.; Prat-Resina, X.; Delgado, E.; Alderete, J. (Proteins: Struct., Funct., Bioinf., 2010)

(untitled) - Xiong, Y.; Liu, J.; Yang, G.-F.; Zhan, C.-G. (J. Comput. Chem., 2010)

(untitled) - Alvarado, O.; Jaña, G.; Delgado, E. J. (J. Comput.-Aided Mol. Des., 2012)

(untitled) - Lizana, I.; Jaña, G. A.; Delgado, E. J. (J. Chem. Inf. Model., 2015)

(untitled) - Sheng, X.; Liu, Y. (Biochemistry, 2013)

(untitled) - Zhang, J.; Sheng, X.; Hou, Q.; Liu, Y. (Int. J. Quantum Chem., 2014)

(untitled) - Zhu, W.; Liu, Y. (Theor. Chem. Acc., 2014)

(untitled) - Sheng, X.; Liu, Y.; Zhang, R. (RSC Adv., 2014)

(untitled) - White, J. K.; Handa, S.; Vankayala, S. L.; Merkler, D. J.; Woodcock, H. L. (J. Phys. Chem. B, 2016)

(untitled) - Nauton, L.; Hélaine, V.; Théry, V.; Hecquet, L. (Biochemistry, 2016)

(untitled) - Sheng, X.; Liu, Y.; Liu, C. (J. Mol. Graphics Mod., 2013)

(untitled) - Metzler, D. E.; Maier, G. D. (Ann. N. Y. Acad. Sci., 1962)

(untitled) - Doughty, M. B.; Lawrence, D. S. (J. Chem. Soc., Chem. Commun., 1985)

(untitled) - Washabaugh, M. W.; Yang, C. C.; Hollenbach, A. D.; Chen, P. (Bioorg. Chem., 1993)

(untitled) - Suzuki, R.; Katayama, T.; Kim, B.-J.; Wakagi, T.; Shoun, H.; Ashida, H.; Yamamoto, K.; Fushinobu, S. (J. Biol. Chem., 2010)

(untitled) - Pang, S. S.; Duggleby, R. G.; Schowen, R. L.; Guddat, L. W. (J. Biol. Chem., 2004)

(untitled) - Guo, F.; Zhang, D.; Kahyaoglu, A.; Farid, R. S.; Jordan, F. (Biochemistry, 1998)

(untitled) - Polovnikova, E. S.; McLeish, M. J.; Sergienko, E. A.; Burgner, J. T.; Anderson, N. L.; Bera, A. K.; Jordan, F.; Kenyon, G. L.; Hasson, M. S. (Biochemistry, 2003)

(untitled) - Brandt, G. S.; Kneen, M. M.; Chakraborty, S.; Baykal, A. T.; Nemeria, N.; Yep, A.; Ruby, D. I.; Petsko, G. A.; Kenyon, G. L.; McLeish, M. J.; Jordan, F.; Ringe, D. (Biochemistry, 2009)

(untitled) - Lohman, K.; Schuster, P. (Biochem. Z., 1937)

(untitled) - Jordan, F.; Nemeria, N. S. (Bioorg. Chem., 2014)

(untitled) - Müller, M.; Gocke, D.; Pohl, M. (FEBS J., 2009)

(untitled) - Nemeria, N. S.; Chakraborty, S.; Balakrishnan, A.; Jordan, F. (FEBS J., 2009)

(untitled) - Bruning, M.; Berheide, M.; Meyer, D.; Golbik, R.; Bartunik, H.; Liese, A.; Tittmann, K. (Biochemistry, 2009)

(untitled) - Nixon, P. F.; Diefenbach, R. J.; Duggleby, R. G. (Biochem. Pharmacol., 1992)

(untitled) - Belenky, I.; Steinmetz, A.; Vyazmensky, M.; Barak, Z.; Tittmann, K.; Chipman, D. M. (FEBS J., 2012)

(untitled) - Patel, H.; Nemeria, N. S.; Brammer, L. A.; Freel Meyers, C. L.; Jordan, F. (J. Am. Chem. Soc., 2012)

(untitled) - Schütz, A.; Golbik, R.; König, S.; Hübner, G.; Tittmann, K. (Biochemistry, 2005)

(untitled) - Wille, G.; Meyer, D.; Steinmetz, A.; Hinze, E.; Golbik, R.; Tittmann, K. (Nat. Chem. Biol., 2006)

(untitled) - Tittmann, K.; Golbik, R.; Uhlemann, K.; Khailova, L.; Schneider, G.; Patel, M.; Jordan, F.; Chipman, D. M.; Duggleby, R. G.; Hübner, G. (Biochemistry, 2003)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

Gaussian 09, Revision D.01 (Gaussian Inc., 2013)

(untitled) - Marenich, A. V.; Cramer, C. J.; Truhlar, D. G. (J. Phys. Chem. B, 2009)